Morfofonemik Prefiks pada Kosakata Bahasa Sula Dialek Fagud - Nurhayati Fokaaya (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
The Affixation Pattern on the Prefix of the Language Vocabulary Structure of the Fagud Dialect includes the prefixes (b-), (b-), di- (bo-), ter (forehead), ke (bo-), (ca-), and per- (smell-). This study aims to determine the Affixation Pattern in the Vocabulary Structure Prefix Sula of Fagud Dialect. The source of this research data is primary data and secondary data. Primary data is obtained directly from speakers or informants, while secondary data is obtained through references, such as magazines, journals, and linguistic reading books related to this paper. The results of this paper can be useful and used as references for language researchers, writers, and language observers.